Konsep Tauhid sebagai Solusi Problematika Pendidikan Agama bagi Siswa Madrasah - M. Hasbi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Â Religious education problems are generally same, with typology lack of internalization process of religious values on student soul. Education is only at religion knowledge level, not at how to practice religion. To eliminate this problems we need alternative solution namely tauhid as religionâ€™s core, that will bring result takwa. Whatever lessons in school, if based on tauhid spirit comprehensively, will give strong impact to lofty character and behavior of students.Â